Caracterização limnológica das cavas geradas pela indústria cerâmica para uso da piscicultura como alternativa de reintegração ambiental - Portela, José Benigno Viana (2004)
This work is based on the environmental study of the armhole originating from clay mines to open, operated by ceramic industries located in the municipality of Bacabeira/MA. We aimed to carry out a preliminary study on environmental quality (soil and water) of the armhole originating from clay extraction for the ceramics industry, for use in fish farming as a form of environmental reintegration. For both a survey was carried out to about the actions of these industries in the city and concomitantly were determined water quality parameters, as well as the leveis of organic matter in the sediment and particle size composition of the soil in six cavas: Cl CP, C2CP, C3CP , Cl SP, C2SP and C3SP. Two seasonal collections were carried out on 01 October and 30 November 2003, and a sampling nictimeral also on 30 November 2003. The results show intense environmental degradation and the lack and / or inadequacy of the practices of mitigating actions. There were thermal stratification, and low conductivity values despite having a basic pH, was low alkalinity, the pH being influenced by high concentrations of ammonia. Dissolved oxygen, suffered great variations from breathing processes, ammonification and nitrification. Micronutrients were high, not being thus limiting factors on productivity of these environments. The NID is still high, the largest contributors being the ammonia nitrogen and nitric nitrogen. These pits can be used for fish farming, provided that management techniques are observed, and the use of species that support the changes in the physico-chemical parameters. However, in this case, the fish can be considered as a complementary agent environmental reintegration